Evaluation of Technical-Vocational Teacher Education Program towards an Academe- and Industry-responsive Curriculum - Alinea, Jess Mark L. (Journal of Technical Education and Training, 2021)
Technical-vocational teachers should adhere to the demands of the academe and the industry. The alignment of the technical and pedagogical skills to the standards set for teaching and working in the industry is necessary for graduates to thrive in the profession. Thus, this study focused on assessing the technical-vocational teacher education program using the lenses of graduates and their respective supervisors in the academe and industry. The study utilised a quantitative research design. It measured the adequacy of the skills acquired by graduates from the curriculum. The general assessments of the Bachelor of Technical-Vocational Teacher Education (BTVTEd) graduates of the curriculum in terms of pedagogical and technical skills were â€œvery adequateâ€ (  = 3.42) and â€œvery usefulâ€ (  = 3.47). On the other hand, the supervisors assessed the graduates in terms of pedagogical and technical skills as â€œvery adequateâ€ (  = 3.40) and â€œvery usefulâ€ (  = 3.45). Graduates and supervisors both have the same assessment of the program. However, the differences in the values of the mean show a slight variation in their perceptions. Based on the findings and conclusion, it is recommended to synchronize the BTVTEd program with the academeâ€™s and industryâ€™s expectations and demands; modification or revision of curriculum is needed. Universities and schools should welcome and entertain inputs from expert graduates and authorities in their respective fields of practice. There is also a need for continuous tracking of graduates at least every five years to monitor their acquired skills and professional advancements in their respective fields, which could be used in crafting an ever-evolving curriculum.